ENTREPRENUERSHIP DALAM PERSPEKTIF ALQURAN DAN ETNOLOGI - Linge, Abdiansyah; Ahmad, Upi Sopiah (BISNIS, 2016)
Alquran is a guidance of life for the people to get prosperity inthe world and beyond, Alquran implement a concept tocombine both of them. Economic activities is also studied inholy quran, where holy quran talk about teory and concept ineconomic system. One of studies that interest in this researchthat have corelation with enterpreneurship, as an eforts todevelope human quality. Many of variable that influencebehaviour of person to do economic activities one of them isculture. This research means to interest the people doenterpreneurship and to increase it by using Alquran asguidance.This study used a qualitative approach, with shadesof library research (library Risearch). This study also aims todetermine the Qur'anic concept of entreprenuership, as well asethnology relation to the formation of a person's interest tobehave entreprenuership. Patterned with qualitative researchliterature research can be concluded: the Qur'an has economictheories with the concept tijarah including entreprenuership.The concept and value of economic value contained in theQur'an into the basic motivation of behavior entreprenuersMuslims, the Qur'an which emphasizes benefit of the people,justice that promotes ethical behavior in each business process,became the basic philosophy in conducting economic activities,including the activities entreprenuership. Second, the idea ofthe results of the concept of human thought and activity in theform of economic behavior contained in a culture that becamehereditary behavior in public when adjusted to the economicvalue contained in the Qur'an will awaken the concept ortheory about sharia entreprenuership.